Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00284-019-01853-y
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Production Behaviors of a Psychrotolerant Histamine-Producer, Morganella psychrotolerans, in Various Environmental Conditions

Abstract: Histamine food poisoning is a major safety concern related to seafood consumption worldwide.Morganella psychrotolerans is a novel psychrotolerant histamine-producer. In this study, the histamine production behaviors of M. psychrotolerans and two other major histamine-producers, mesophilic Morganella morganii and psychrotrophic Photobacterium phosphoreum, were compared in seafood products, and histamine accumulation by M. psychrotolerans was characterized at various pH and temperature levels in culture broth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Although P. phosphoreum and P. iliopiscarium have been largely described as histamine producers on fish ( Bjornsdottir-Butler et al., 2018 ; Bjornsdottir et al., 2009 ; Kanki et al., 2004 ), and the histamine production of several fish-isolated strains previously measured ( López Caballero et al., 2002 ; Morii and Kasama, 2004 ; Torido et al., 2012 ; Wang et al., 2020 ), we did not detect presence of the hdc gene in any of the screened isolates, also reported by Machado and Gram, 2017 . Measured production of histamine in some of the isolates included in this study (AK-3, AK-8, FS-1.1, FS-1.2, FS-2.1, FS-4.2), reported by Bjornsdottir-Butler et al., 2018 , might be due to the presence of an alternative histidine decarboxylase gene ( hdc 2) recently identified by Bjornsdottir-Butler et al., 2020 .…”
Section: Discussioncontrasting
confidence: 55%
“…Although P. phosphoreum and P. iliopiscarium have been largely described as histamine producers on fish ( Bjornsdottir-Butler et al., 2018 ; Bjornsdottir et al., 2009 ; Kanki et al., 2004 ), and the histamine production of several fish-isolated strains previously measured ( López Caballero et al., 2002 ; Morii and Kasama, 2004 ; Torido et al., 2012 ; Wang et al., 2020 ), we did not detect presence of the hdc gene in any of the screened isolates, also reported by Machado and Gram, 2017 . Measured production of histamine in some of the isolates included in this study (AK-3, AK-8, FS-1.1, FS-1.2, FS-2.1, FS-4.2), reported by Bjornsdottir-Butler et al., 2018 , might be due to the presence of an alternative histidine decarboxylase gene ( hdc 2) recently identified by Bjornsdottir-Butler et al., 2020 .…”
Section: Discussioncontrasting
confidence: 55%
“…In previous studies, the link between the cases of histamine poisoning and seafood contaminated with M. psychrotolerans has been reported (Dalgaard, Emborg, Kjølby, Sørensen, & Ballin, 2008;Emborg & Dalgaard, 2006;Emborg, Laursen, & Dalgaard, 2005). In our previous studies, we revealed the presence of M. psychrotolerans in retail seafood distributed in Japan (Kato et al, 2017) and also showed that M. psychrotolerans had high histamine-producing abilities (Wang, Yamaki, Kawai, & Yamazaki, 2020). Therefore, controlling M. psychrotolerans populations in seafood is a major challenge faced by the seafood industry.…”
Section: Introductionmentioning
confidence: 88%
“…Histamine is produced by proteolytic bacteria from the decarboxylation of the amino acid histidine [ 6 , 11 ]. The concentration of histamine in food depends on the histidine contents present and on the presence of microorganisms belonging to the genera Vibrio, Photobacterium, Klebsiella , and Morganella in tissues [ 12 ]. In predisposed individuals, even small doses (e.g., 50 mg kg −1 ) can lead to poisoning [ 13 ].…”
Section: Introductionmentioning
confidence: 99%